Replication dynamics of recombination-dependent replication forks - Karel Naiman (Nature Portfolio, 2021)
Replication forks that are stalled at obstacles on the DNA template can be restarted by homologous recombination. Here, the authors show replication dynamics during homologous recombination-dependent replication fork restart by combining polymerase usage sequencing and a Monte Carlo mathematical model.